STUDI FAKTOR POPULARITAS VTUBER GENERASI Z DENGAN METODE MULTI-ANALISIS DI KOTA BATAM - Diny Anggraini Adnas; Dyon Andrean (JURNAL ILMIAH BETRIK, 2023)
This study aims to analyze the factors that influence the popularity of VTuber in generation Z in Batam City. The multi-analytic method used includes surveys and interviews. The results of the study show that the factors that influence the popularity of VTuber include beauty or good looks, communication skills, and entertaining content. In addition, other factors such as partnerships with brands and interactions with fans also play an important role in determining the popularity of a VTuber. An important contribution of this research is to provide a more in-depth view of the factors influencing the popularity of VTuber, which can be used by industry players to improve their marketing strategies.